HUBUNGAN PENGETAHUAN DAN DUKUNGAN SUAMI DENGAN KECEMASAN IBU HAMIL TRIMESTER III MENGHADAPI PERSALINAN PADA MASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS BERSERI PANGKALAN KERINCI - Siti Romlah; Ekry Binti Farizal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Anxiety appears in the third trimester (28-40 weeks) starting before delivery. In addition, this third trimester is a lot of risk that the possibility of premature birth so that it can cause high anxiety in pregnant women before delivery. The purpose of the study was to determine the relationship between husband's knowledge and support with the anxiety of third trimester pregnant women facing the Covid-19 pandemic in the Puskesma Berseri Health Center Work Area. The type of research used in this study was quantitative with a cross sectional design. This research was carried out from August to September 2021 in the Work Area of the Puskesmas Berseri, The study population was third trimester pregnant women with a total sample of 51 people. Data processing is done by computerization with univariate and bivariate analysis. Univariate results showed that 31 respondents (60.8%) had poor knowledge, 29 respondents had less husband support and 23 respondents (56.9%) experienced anxiety. The results of bivariate knowledge have a relationship between (p.value = 0.001) and husband's support (p.value = 0.002) with the anxiety of pregnant women in the third trimester facing childbirth during the Covid-19 pandemic. It is recommended for the Puskesmas to improve the counseling program in the future by using leaflet media to increase the knowledge of pregnant women, namely by providing information and counseling to the community about preventing Covid 19 at the time of delivery.